Science forum: The human cell atlas - Regev, Aviv; Eils, Roland (eLife, 2017)
Advances in techniques for analysing single cells and tissues have inspired an international effort to create comprehensive reference maps of all human cells - the fundamental units of life - as a basis for both understanding human health and diagnosing, monitoring and treating disease.
Gesehen am 26.04.2018